(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
This study determined practical effective principals’ leadership behaviours and today’s teacher task performance in secondary schools in Anambra State. Guided by one research question and one null hypothesis tested at the 0.05 level of significance, the correlational survey research design was adopted in this study. Population of the study comprised all the 263 principals and 5,249 secondary school teachers in all the public secondary schools in the six education zones of the state. Using multistage sampling procedure, a sample of 350 respondents was drawn. Data was collected using two researchers’ developed questionnaires titled, “Practical Effective Principals’ Leadership Behaviours Questionnaire” (PEPLBQ) and “Today’s Teacher Task Performance Questionnaire” (TTPQ). The two questionnaires were structured on a four-point response scale of Strongly Agree (SA), Agree (A), Disagree (D) and Strongly Disagree (SD), weighted 4, 3, 2, and 1 respectively. The instruments were validated by four experts. The internal consistency of the questionnaires was determined using Cronbach’s Alpha method and it yielded reliability coefficients of 0.78 and 0.76 for PEPLBQ and TTPQ respectively. The research question was answered using Pearson’s Product Moment Correlation, while p-value was used to determine the significance of the correlation at the 0.05 level of significance. The result of the study showed that there is a very high positive and significant relationship between practical principals’ leadership behaviours and today’s teacher task performance in secondary schools in Anambra State. Based on the findings, it was recommended that capacity building workshop on practical effective principals’ leadership behaviours should be organized for the principals to remind and encourage them to consistently exhibit such practical and effective leadership behaviours for improved today’s teacher job performance and consequently, quality secondary education in the state.